Factors Responsible for Delayed Diagnosis of Carcinoma Gallbladder - Bar, Debashish; Alam, Abul Bashar Mohammed Khurshid; Chowdhury, Md Mohsen; Das, Bidhan Chandra; Mahmud, Ashik; Suzana, Nawreen (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Gallbladder cancer typically remains silent until an advanced and often noncurative stage with the shortest median survival after diagnosis. This poor prognosis is due to an aggressive biologic behavior and a lack of sensitive screening tests for early detection resulting in delayed diagnosis at advanced stage. This study was conducted to find out the factors responsible for diagnosis of carcinoma gallbladder at advanced stage. Materials and Methods: This observational study was conducted in BSMMU from July 2022- June 2023 on 110 patients of carcinoma gallbladder. The patients were grouped into early (stage I, II) and advanced stage (stage III, IV) on the basis of imaging or histopathology report. All the variables related to diagnosis of carcinoma gallbladder were evaluated and factors related to delayed diagnosis were found out. Results: Most of the patients of this study group (60%) were diagnosed at advanced stage. Among the patients with advanced carcinoma gallbladder, 82% reported from rural area, 54% were from low income family and 95% patients’ educational status was up to HSC. Early gallbladder carcinoma mainly presented with pain (44%) and jaundice (31%) which resembles benign disease and Imaging findings of these patients were only GB wall thickening which does not strongly raise the suspicion of malignancy. In early gallbladder carcinoma group CA 19-9 and CEA were not significantly raised (32% and 25% respectively). Conclusion: Rural residence, low educational level and poor economic status of the people of our study group; lack of specific symptom, sensitive imaging study and specific tumour marker at early stage of the disease was responsible for delayed diagnosis of carcinoma gallbladder at advanced stage. J Bangladesh Coll Phys Surg 2025; 43: 255-160